Enhancing Digital Literacy Skills among Secondary School Students in Quetta: Challenges, Gaps, and Policy Directions - Yasmeen, Fiza; Kiazai , Dr. Abdul Nasir; Ahmed, Pervez (Journal of Quranic and Social Studies, 2025)
The importance of digital literacy for academic achievement, job readiness, and civic engagement in the knowledge economy of the twenty-first century is becoming more widely acknowledged. Digital literacy is still lacking in many developing nations, especially in Pakistan’s Baluchistan, despite its worldwide importance. This study examines the present state of digital literacy among Quetta secondary school students, pinpoints obstacles that educators and students encounter, and suggests methods for improving digital competencies. 138 students were tested on their proficiency in six ICT domains using a quantitative design and the Digital Literacy Assessment Tool (DLAT), which was modified from the European Union framework. These domains included Microsoft applications, multimedia tools, communication platforms, problem-solving, content access, and cyber security. Additionally, 133 teachers’ survey responses were gathered in order to assess the difficulties associated with ICT integration. The findings demonstrate a good level of proficiency with communication tools (66.6% at the advanced level) and a respectable level of ability with multimedia applications and material access. However, serious deficiencies were discovered in problem-solving (89% beginning) and cyber security (59% novice). Teacher polls revealed a number of systemic barriers, including ambiguous ICT policies, poor infrastructure, a lack of funding, a lack of professional development, and cultural resistance to technology use. Even if kids get some basic digital exposure informally, the study concludes that there is a lack of systematic and pedagogically integrated ICT training. To reduce the digital gap, the research recommends curriculum changes that align with worldwide frameworks, continuous professional development for educators, increased infrastructure investment, digital material that is relevant for the region, and cyber security awareness initiatives. These adjustments are necessary to give Baluchistan’s children the tools they need to thrive in the digital era, which will enhance employability, equity, and national growth.